P19 The Role Of Differential Tnfr Signalling In Maintenance Of Alveolar Epithelial Homeostasis. (10th November 2014) - Millar, FR; Proudfoot, AG; Salman, D; Summers, C; Morley, P; Cordy, J; Bayliffe, A; Dean, C; Griffiths, MJ
Abstract : Alveolar epithelial activation and disruption of the alveolar epithelial barrier promote recruitment of neutrophils into the alveolar space and cause alveolar oedema respectively thereby playing key roles in the pathogenesis of Acute Respiratory Distress Syndrome (ARDS). Tumour necrosis factor alpha (TNF) is an early mediator of inflammation in ARDS. TNF signals through two cell surface receptors, TNFR1 and TNFR2 initiating distinct signalling pathways and cellular responses. Using a novel, highly selective TNFR1 domain antibody (dAb™), a dummy dAb and the dual TNFR antagonist Adalimumab™, we investigated the role of differential TNFR signalling on human pulmonary alveolar epithelial cell (human alveolar type 2 cells and A549 cell line) activation, permeability and repair. Human alveolar epithelial type 2 cells (haT2) expressed both TNFR, whilst A549 cells only expressed TNFR1. TNFR1 signalling mediated release of the neutrophil chemokines IL-8 and GMCSF as well as IL-6 in hAT2 (pin vitro scratch model of epithelial (haT2) wound repair. TNFR1 signalling induced pro-inflammatory cytokine expression from alveolar epithelial cells and mediated increased epithelial permeability. TNFR1 induced permeability did not appear to be due to disruption of epithelial junctional proteins; we speculate that this may alternatively be due to TNFR1 induced cell death.